How Preservice Teachers Begin to Develop Equitable Visions for Teaching Multilingual Learners. Issue 4 (8th August 2021) - Deng, Qizhen; Hayden, H. Emily
ABSTRACT: Given the growing numbers of multilingual learners in public school classrooms and persistent nationwide shortages of ESL-endorsed teachers, it is essential that preservice teachers (PSTs) are prepared to teach multilingual learners in equitable, effective ways. Visioning can help with this, but before developing visions that include being teachers of multilingual learners, PSTs must first develop metacognitive awareness of their beliefs about multilingualism and multilingual learners in the classroom. Using historically situated social practice and translanguaging pedagogy as framing, this study surveyed final-year PSTs pursuing elementary education or special education certification on four dimensions of beliefs about multilingualism: embracing the interconnected nature of language with culture and identity, valuing multilingualism, understanding language demand in content classrooms, and feeling responsible for language teaching. Results revealed contradictory beliefs about multilingual learners that were influenced by PSTs' backgrounds and experiences, including whether they were pursuing an ESL endorsement and their second language proficiency. We call on teacher preparation programs to re-examine their curriculum in order to better prepare all PSTs to work with multilingual learners. Teacher educators can begin this work by helping PSTs become metacognitive about their beliefs as an essential first step to developing equitable visions for teaching multilingual learners.